A simple model of the long-term interest rate - Tanweer Akram (Levy Economics Institute of Bard College, 2020)
This paper presents a simple model of the long-term interest rate. The model represents John Maynard Keynes's conjecture that the central bank's actions influence the long-term interest rate primarily through the short-term interest rate, while allowing for other important factors. It relies on the geometric Brownian motion to formally model Keynes's conjecture. Geometric Brownian motion has been widely used in modeling interest rate dynamics in quantitative finance. However, it has not been used to represent Keynes's conjecture. Empirical studies in support of the Keynesian perspective and the stylized facts on the dynamics of the long-term interest rate on government bonds suggest that interest rate models based on Keynes's conjecture can be advantageous.
Keywords: E12; E43; E50; E58; E60; G10; G12; G41; 330; Long-Term Interest Rate; Bond Yields; Monetary Policy; Short-Term Interest Rate; John Maynard Keynes